Advances in Microengineered Platforms for Skin Research - Sireesh Kumar Teertam; Vijayasaradhi Setaluri; Jose M. Ayuso (JID Innovations)
The skin plays a critical role in human physiology, acting both as a barrier to environmental insults and as a window to environmental stimuli. Disruption of this homeostasis leads to numerous skin disorders. Human and animal skin differ significantly, limiting the translational potential of animal-based investigations to advance therapeutics to human skin diseases. Hence, there is a critical need for physiologically relevant human skin models to explore novel treatment strategies. Recent advances in microfluidic technologies now allow design and generation of organ-on-chip devices that mimic critical features of tissue architecture. Skin-on-a-chip and microfluidic platforms hold promise as useful models for diverse dermatology applications. Compared with traditional in vitro models, microfluidic platforms offer improved control of fluid flow, which in turn allows precise manipulation of cell and molecular distribution. These properties enable the generation of multilayered in vitro models that mimic human skin structure while simultaneously offering superior control over nutrient and drug distribution. Researchers have used microfluidic platforms for a variety of applications in skin research, including epidermal–dermal cellular crosstalk, cell migration, mechanobiology, microbiome–immune response interactions, vascular biology, and wound healing. In this review, we comprehensively review state-of-the-art microfluidic models for skin research. We discuss the challenges and promise of current skin-on-a-chip technologies and provide a roadmap for future research in this active field.